Legislating Phonics: Settled Science or Political Polemics?. Issue 1 (January 2023) - Reinking, David; Hruby, George G.; Risko, Victoria J.
In this commentary, we identify a phonics-first ideology and its polemical distortions of research and science to promote legislation that constrains and diminishes the teaching of reading. We affirm our own, and a majority of reading professionals', commitment to teaching phonics. However, we argue that phonics instruction is more effective when embedded in a more comprehensive program of literacy instruction that accommodates students' individual needs and multiple approaches to teaching phonics—a view supported by substantial research. After summarizing the politicization of phonics in the United States, we critique a legislated training course for teachers in Tennessee as representative of how a phonics-first ideology is expressed polemically for political purposes. We contrast it with a more collaboratively developed, balanced, nonlegislative approach in the previous governor's administration. Specifically, the training course (a) makes an unfounded claim that there is a national reading crisis that can be traced to insufficient or inappropriate phonics instruction; (b) distorts, misrepresents, or omits relevant research findings and recommendations, most prominently from the report of the National Reading Panel; (c) inaccurately suggests that "balanced literacy instruction" is "whole language" instruction in disguise; and (d) wrongly claims that its views of phonics are based on a settled science of reading.